The Image of the Iraqi Soldier in British Media: A Critical Discourse Analysis (مجلة ديالى للبحوث الانسانية, 2023)
AbstractThe security situations witnessed in Iraq after 2003 were mainly characterized by instability. This represented a great challenge for Iraqi forces to impose security, and protect citizens. This has increasingly made the international medias in general and British media in particular shed light on the Iraqi situations including Iraqi soldiers. This has led to the emergence of a real research gap represented by some important questions regarding the nature of the British media's attitude towards the Iraqi soldiers. so, this study is an attempt to reveal the image of the Iraqi soldiers in British media.The study is based on the hypothesis that IS in general is depicted positively in British media at both Mil and Mal levels". To achieve the aims of the study and verify its hypothesis, two types of procedures have been followed: theoretical and practical. The theoretical procedure consists of presenting a theoretical framework of critical discourse analysis including its basic concepts, approaches, models of analysis.  On the other hand, the practical procedure consists of selecting three British articles from The Sun, BBC News and the Daily Mail. The selected articles have been analyzed in the light of an adapted form of van Dijk 's model (2000).